Predictive Significance of Combined Plasmatic Detection of BRAF Mutations and S100B Tumor Marker in Early‐Stage Malignant Melanoma - Jiri Polivka; Mohamed A. Gouda; Mahyar Sharif; Martin Pesta; Helen Huang; Inka Treskova; Vlastimil Woznica; Jindra Windrichova; Katerina Houfkova; Radek Kucera; Tomas Fikrle; Jan Ricar; et al. (Cancer Medicine)
ABSTRACT Background Melanoma is the most aggressive skin cancer with ability to recur also after early‐stage tumor surgery. The aim was to identify early‐stage melanoma patients at high risk of recurrence using liquid biopsy, estimating of mutated BRAF ctDNA and the level of tumor marker S100B in plasma. Methods Eighty patients were enrolled in the study. BRAF V600E mutation was determined in FFPE tissue and plasma samples using ultrasensitive ddPCR with pre‐amplification. The level of S100B was determined in plasma by immunoassay chemiluminescent method. Results The best prediction of melanoma recurrence after surgery was observed in patients with combined high level of S100B (S100Bhigh) and ctDNA BRAFV600E (BRAFmut) in preoperative (57.1% vs. 12.5%, p = 0.025) as well as postoperative blood samples (83.3% vs. 14.3%, resp., p = 0.001) in comparison with low S100B and BRAF wild‐type. Similarly, patients with preoperative and postoperative S100Bhigh and BRAFmut experienced worse prognosis (DFI p = 0.05, OS p = 0.131 and DFI p = 0.001, OS = 0.001, resp.). Conclusion We observed the benefit of the estimation of combination of S100B and ctDNA BRAFmut in peripheral blood for identification of patients at high risk of recurrence and unfavorable prognosis. Significance There is still no general consensus on molecular markers for deciding the appropriateness of adjuvant treatment of early‐stage melanoma. We have shown for the first time that the combined determination of the ctDNA BRAFmut oncogene (liquid biopsy) and the high level of tumor marker S100B in pre‐ and postoperative plasma samples can identify patients with the worst prognosis and the highest risk of tumor recurrence. Therefore, modern adjuvant therapy would be appropriate for these patients with resectable melanoma, regardless of disease stage.